Genotypic variation for nitrogen-use efficiency in rapeseed-mustard (Journal of Oilseed Brassica, 2026)
Genetic variation for nitrogen-use efficiency (NUE) and related yield traits were assessed in 11 toria (Brassica rapa var. toria), 14 yellow sarson (Brassica rapa var. yellow sarson) and 7 Indian mustard (Brassica juncea) genotypes. These genotypes were evaluated at 0 and 40 kg N ha-1 levels of nitrogen fertilization and, nitrogen-use efficiency (NUE) in terms of agronomic efficiency was determined. Significant genetic variation was observed for all the traits studied. A toria genotype TS65 produced the highest yield (9.92 q/ha) coupled with the highest NUE (17.5 kg kg-1). High heritability was recorded for leaf nitrogen, 1000-seed weight, nitrate reductase activity (NRA), days to maturity, siliquae per plant and seeds per siliqua. High genetic advance was recorded for siliquae number per plant, NRA, seeds per siliqua and leaf N. There was strong positive genetic correlation between seed yield and NUE, indicating the significance of enhanced NUE for seed yield improvement.